The Possibility Of Applying The New York Convention To Recognise And Enforce The Foreign Arbitration Awards In Petroleum Disputes In Iraq - Mohammed, Haitham Abdulwahhab (Comite Cientifico Interinstitucional, 2023)
Objective: This study seeks to analyse how the New York Convention for the Recognition and Enforcement of Foreign Arbitration Awards can be applied to the recognition and enforcement of foreign arbitration awards in petroleum disputes in Iraq.